Effect of irrigation regimes and nitrogen levels on herbage and oil yield, oil quality,nutrient uptake and economics of lemongrass (Cymbopogon flexuosus) in a sandy loam soil of Orissa - CHAKRABORTY, H; SETHI, R R; BRAHMANAND, P S; MANDAL, K G; SINGANDHUPE, R B; KUMAR, A (The Indian Journal of Agricultural Sciences, 2010)
Field experiment was conducted during (2005–07) in a sandy loam soil at Bhubaneswar,Orissa to study the effect of 2 different irrigation regimes (irrigation at 1.0 and 0.5 IW/CPE) and 4 nitrogen rates (0, 30, 60 and 90 kg N/ha/year) on the herbage yield, oil yield, nitrogen uptake and oil quality of ‘OD-19’ lemongrass [Cymbopogon flexuosus (Steud.) J.F.Wats.]. Herbage and oil yield under the irrigation level I1 (irrigation at 1.0 IW/CPE) was more than that under I2 (irrigation at 0.5 IW/CPE) by 13, 19, 12 and 13% in the second, third, fifth and sixth harvests, respectively. The increased rate of N application up to 90 kg N/ha/year has resulted in an increase in nitrogen uptake by 38.8, 60.4 and 80.4% in N30, N60 and N90, respectively over the N0. However, ‘citral a’ and ‘citral b’ showed no variation in relation to irrigation regimes and nitrogen rates. The benefit : cost ratio was found to be superior with treatment receiving irrigation at 0.5 IW/CPE and N rate @ 90 kg/ha/year in both the years with 1.68 in 2005–06 and 2.99 in 2006–07.